Control of carbohydrate processing: increased beta-1,6 branching in N-linked carbohydrates of Lec9 CHO mutants appears to arise from a defect in oligosaccharide-dolichol biosynthesis. - Rosenwald, A G (1989)
A correlation between increased beta-1,6 branching of N-linked carbohydrates and the ability of a cell to metastasize or to form a tumor has been observed in several experimental models. Lec9 Chinese hamster ovary (CHO) mutants exhibit a drastic reduction in tumorigenicity in nude mice, and this phenotype directly correlates with their ability to attach an increased proportion of beta-1,6-branched carbohydrates to the G glycoprotein of vesicular stomatitis virus (J. Ripka, S. Shin, and P. Stanley, Mol. Cell. Biol. 6:1268-1275, 1986). In this paper we provide evidence that cellular carbohydrates from Lec9 cells also contain an increased proportion of beta-1,6-branched carbohydrates, although they do not possess significantly increased activity of the beta-1,6 branching enzyme (GlcNAc-transferase V). Biosynthetic labeling experiments show that a substantial degree of underglycosylation occurs in Lec9 cells and that this affects several classes of glycoproteins. Lec9 cells synthesize ca. 40-fold less Glc3Man9GlcNAc2-P-P-lipid and ca. 2-fold less Man5GlcNAc2-P-P-lipid than parental cells do. In addition, Lec9 cells possess ca. fivefold less protein-bound oligosaccharide intermediates, and one major species is resistant to release by endo-beta-N-acetylglucosaminidase H (endo H). Membranes of Lec9 cells exhibit normal mannosylphosphoryldolichol synthase, glucosylphosphoryldolichol synthase, and N-acetylglucosaminylphosphate transferase activities in the presence of exogenous dolichyl phosphate. However, in the absence of exogenous dolichyl phosphate, mannosylphosphoryldolichol synthase and glucosylphosphoryldolichol synthase activities are reduced in membranes of Lec9 cells, indicating that membranes of Lec9 cells are deficient in lipid phosphate. This was confirmed by analysis of lipids labeled by [3H]mevalonate, which showed that Lec9 cells have less lipid phosphate than parental CHO cells. Mechanisms by which a defect in the synthesis of dolichol-oligosaccharides might alter the degree of beta-1,6 branching in N-linked carbohydrates are discussed.